Problems in Food Security Data Collection Practices with an illustration from northern Ghana - Rancatore, Jason (The International Journal of Sociology of Agriculture and Food, 2022)
Solutions to food security issues at all levels typically include a call for more and better data. This paper finds that food security data problems are only partially remedied by gathering more data or applying new and innovative metrics. Examination of various research in Ghana covering published academic work as well as the World Food Programme’s reporting at both the country and sub-state levels reveals some fundamental problems (both practical and theoretical). Coupled with the author’s observations of a market operation in northern Ghana, evidence suggests that these issues are overlooked in order to serve an institutional demand for more data. The paper concludes with a discussion of implications focusing on three ideas: differentiating issue management and knowledge production, reconsidering methodology, and local-level understandings.